Anti-corrosion anti-cavitation self-repairing marine protective coating applicable to high-temperature environment and preparation method of anti-corrosion anti-cavitation self-repairing marine protective coating

By combining functionalized carbon nanotubes with polyurethane and introducing chain extenders, the corrosion and cavitation resistance in high-temperature environments are improved, and the problems of insufficient toughness and tensile strength of existing coating materials are solved, achieving significant results Improves protection performance and self-healing ability.

CN119505669AInactive Publication Date: 2025-02-25JILIN UNIVERSITY

Patent Information

Application Number
CN202411631420.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing self-healing polyurethane high-temperature corrosion-resistant and cavitation-resistant coatings still have room for improvement in corrosion and cavitation-resistant performance under high-temperature environments. The material toughness and tensile strength are insufficient, which affects the protection effect.

Method used

Functionalized carbon nanotubes (FMWCNTs) and polyurethane (PU) are combined to improve the dispersion and binding of carbon nanotubes through surface modification, and the chain extender glycosamine-furyl glycidyl ether glycol (FA-FGE) is introduced. Diol) to improve self-healing performance.

Benefits of technology

The corrosion-proof and cavitation resistance of the coating is significantly improved, the material toughness and tensile strength are both improved, the self-healing rate reaches 93% under infrared light, and the self-healing rate remains at 81% after three repetitions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505669A_ABST
    Figure CN119505669A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant cavitation-erosion-resistant self-repairing marine protective coating suitable for a high-temperature environment and a preparation method thereof, belongs to the technical field of marine protective coatings, and aims to further improve the comprehensive performance of existing self-repairing polyurethane. FA-FGE diol is used as a chain extender, and on the basis of a DA bond, the corrosion-resistant cavitation-erosion-resistant self-repairing marine protective coating suitable for the high-temperature environment and the preparation method of the corrosion-resistant cavitation-erosion-resistant self-repairing marine protective coating are prepared. A hydrogen bond is used as a supplement to adjust the content of a chain extender according to different molar ratios, and is introduced into a PU system to obtain self-repairing performance. The dopamine is used for performing surface modification on the carbon nano tube, so that the binding property and the dispersity of the dopamine modified carbon nano tube and a polyurethane interface are improved, and the overall protection performance of the material is improved. Tests show that the material toughness of the coating can reach 356 MJ / m < 3 >, and the tensile strength can reach 72 MPa. Compared with previous reports, the corrosion resistance and cavitation erosion resistance are remarkably improved, the self-healing rate under infrared light for 90 s is 93%, and the self-healing rate after repeating for 3 times is 81%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of marine protective coatings. Background Art

[0002] Corrosion is a major problem facing marine equipment and underwater facilities. When corrosion occurs, the underwater surface deteriorates rapidly, affecting the health of the underwater surface and significantly increasing maintenance costs. In severe cases, it can also cause serious safety accidents, resulting in significant economic losses and unbearable consequences. Cavitation, also often called cavitation, refers to the phenomenon that cave-like corrosion damage occurs on the solid surface in contact with the fluid under high-speed flow and pressure changes. This phenomenon often occurs in propellers, seawater pipelines, etc. There are some high-temperature environments in the ocean, such as the ocean splash zone, drainage pipes of nuclear power plants, impellers, etc. The corrosion and cavitation rates of the surface are higher at high temperatures, which puts higher requirements on high-performance coatings.

[0003] In order to achieve anti-corrosion and anti-cavitation performance, current underwater surfaces usually use a variety of coating stacking methods. For example, the propeller protective coating is usually composed of anti-corrosion primer, elastic buffer paint, intermediate connecting paint, and anti-fouling topcoat. The anti-corrosion primer and elastic buffer paint have anti-corrosion and anti-cavitation functions respectively. However, the protection function is achieved by stacking multiple coatings, which makes the construction more complicated and the cost higher.

[0004] Polyurethane (PU) is a widely used coating substrate with certain elasticity and can absorb cavitation energy, thus showing anti-cavitation performance. Functionalized MWCNTs reinforced multifunctional self-healing polyurethane coating for high-temperature anti-corrosion and anti-cavitation applications (https: / / doi.org / 10.1016 / j.cej.2024.156326) proposes a carbon nanotube-reinforced self-healing polyurethane high-temperature anti-corrosion and anti-cavitation coating. The addition of carbon nanotubes gives it good protective and mechanical properties, but its material toughness, tensile strength and other properties that affect the anti-corrosion and anti-cavitation effects need to be further improved, so as to improve its comprehensive performance. Summary of the invention

[0005] In order to further improve the comprehensive performance of the existing self-repairing polyurethane, the present invention proposes an anti-corrosion and anti-cavitation self-repairing marine protective coating suitable for high temperature environments. The technical scheme adopted is as follows: A method for preparing an anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments, the specific steps are as follows: 1) Add 1.85-3.17 mmol of polytetramethylene diol (PTMG) with a molecular weight of 1000 g / mol and 4.4 mmol of diphenylmethane diisocyanate (4,4′-Methylene diphenyl diisocyanate, MDI) into a reaction container, and add ethyl acetate (EA) to reduce the viscosity of the reactants, then stir the mixture and heat it at 70°C for 4 hours under a nitrogen atmosphere to obtain a PU prepolymer; 2) Stirring the PU prepolymer at room temperature for 4 hours, then adding 1.845~3.825mmol of diphenylmethane bismaleimide (N, N'-(4,4'-Methylene-diphenyl)bismaleimide, BMI) and 1.23~2.55mmol of chain extender glycosylamine-furfuryl glycidyl ether diol (FA-FGE Diol) to the PU prepolymer, stirring for 1h to obtain a PU solution; at the same time, adding 1~5wt% of the mass of the PU prepolymer to N, N-dimethylformamide (N,N-dimethylformamide, DMF), and ultrasonically treating for 1h to obtain a FMWCNTs / MDF blend; then mixing the FMWCNTs / MDF blend with the PU solution, and ultrasonically treating for 1h to obtain a coating; the functionalized carbon nanotubes are dopamine-modified carbon nanotubes; 3) The coating is coated on the substrate, and after curing, the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments is obtained.

[0006] Preferably, the amount of polytetrahydrofuran diol added in step 1) is 2.73 mmol.

[0007] Preferably, in step 2), the amount of diphenylmethane bismaleimide added is 2.505 mmol.

[0008] Preferably, in step 2), the amount of the chain extender glucosamine-furfuryl glycidyl ether diol added is 1.67 mmol.

[0009] Preferably, the preparation steps of the chain extender glucosamine-furfuryl glycidyl ether diol in step 2) are as follows: First, furfuryl amin (FA) and furfuryl glycidyl ether (FGE) were added into a reaction vessel at a molar ratio of 1:2, and then N, N-dimethylformamide was added to reduce the viscosity of the reactants. The reaction was then carried out at 80°C for 6 hours to finally obtain the chain extender glycosylamine-furfuryl glycidyl ether diol (FA-FGE Diol).

[0010] Preferably, the amount of functionalized carbon nanotubes added in step 2) is 1 wt %.

[0011] Preferably, the preparation steps of the functionalized carbon nanotubes in step 2) are as follows: 400 mg of multi-walled carbon nanotubes (MWCNTs) were ultrasonically mixed with 80 mL of Tris-butter solution in a beaker for 30 minutes, and then 160 mg of dopamine hydrochloride was added and stirred for 12 hours. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol three times, and dried under vacuum at 60°C to obtain functionalized carbon nanotubes.

[0012] Beneficial effects of the present invention: Materials such as carbon nanotubes have high surface energy and are prone to agglomeration when dispersed in a material system. The present invention uses polydopamine carbon to modify the surface of the nanotubes. Since dopamine has strong adhesion, the binding and dispersibility of the dopamine-modified carbon nanotubes with the polyurethane interface are improved, thereby improving the overall protective performance of the material.

[0013] In addition, the synthesized FA-FGE diol chain extender is based on DA bonds and supplemented by hydrogen bonds. The content of the chain extender is adjusted at different molar ratios and introduced into the PU system to obtain self-healing properties. According to the test, the material toughness of the coating of the present invention can reach 356 MJ / m 3 , the tensile strength can reach 72 MPa, which is better than similar materials in the literature. Compared with the previously reported carbon nanotube-reinforced self-healing polyurethane high-temperature anti-corrosion and anti-cavitation coating (https: / / doi.org / 10.1016 / j.cej.2024.156326), the anti-corrosion and anti-cavitation properties of the present invention are significantly improved, and the self-healing rate is 93% in 90 s under infrared light, and the self-healing rate after 3 repetitions is 81%. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of self-healing polyurethane; Figure 2 Preparation of functionalized carbon nanotubes; Figure 3 Mass loss rate of sample in water; Figure 4 Self-repair test results; Figure 5 Anti-corrosion performance test results; Figure 6 Cavitation resistance of PU2 and PU-FM samples at 20°C and 80°C; Figure 7 Tensile strength test data; Figure 8 Tensile strength test data after self-repair. DETAILED DESCRIPTION

[0015] The technical solution of the present invention is further explained and illustrated in the form of specific embodiments below.

[0016] Example 1 Synthesis of functionalized carbon nanotubes (FMWCNTs) like Figure 2 As shown, 400 mg of carbon nanotubes (MWCNTs) were ultrasonically mixed with 80 mL of Tris-butter solution in a beaker for 30 minutes, and then 160 mg of dopamine hydrochloride was added and stirred for 12 hours. After the reaction, the mixture was centrifuged, washed with deionized water and ethanol three times, and dried in vacuum at 60°C to obtain functionalized carbon nanotubes (FMWCNTs).

[0017] Example 2 Synthesis of self-healing polyurethane coating 1) First, furfuryl amin (FA) and furfuryl glycidyl ether (FGE) were added into a reaction bottle at a molar ratio of 1:2, and then dimethylformamide (N, N-dimethylformamide, DMF) was added to reduce the viscosity of the reactants, and then the reaction was carried out at 80°C for 6 hours to finally obtain the chain extender glycosylamine-furfuryl glycidyl ether diol (FA-FGE Diol).

[0018] 2) 2.73 mmol of polytetrahydrofuranglycol (PTMG, Mw = 1000 g / mol) and 4.4 mmol of diphenylmethane diisocyanate (4,4′-Methylenediphenyl diisocyanate, MDI) were added to a round-bottom flask, and ethyl acetate (EA) was added to reduce the viscosity of the reactants. The mixture was then stirred and heated at 70°C for 4 hours under a nitrogen atmosphere to obtain a PU prepolymer.

[0019] 3) The PU prepolymer was stirred at room temperature for 4 hours, and then 2.505mmol of an exact amount of diphenylmethane bismaleimide (N, N'-(4,4'-Methylene-diphenyl)bismaleimide, BMI) and 1.67mmol of a chain extender FA-FGE Diol were added to the PU prepolymer and stirred for 1h to obtain a PU solution. At the same time, FMWCNTs accounting for 1wt% of the mass of the PU prepolymer were added to DMF and ultrasonically treated for 1h to obtain a FMWCNTs / MDF blend. The FMWCNTs / MDF blend was then mixed with the PU solution, ultrasonically treated for 1h, and then poured into a polytetrafluoroethylene mold. Finally, the synthesis was completed by drying at 80°C for 24h in a vacuum drying oven to obtain the sample PU-FM.

[0020] Embodiment 3~6 The difference between Examples 3 to 6 and Example 2 is that: 2) Add 3.17 mmol, 2.73 mmol, 2.30 mmol, and 1.85 mmol of polytetrahydrofuran glycol (PTMG, Mw = 1000 g / mol) and 4.4 mmol of diphenylmethane diisocyanate (4,4′-Methylene diphenyl diisocyanate, MDI) into a round-bottom flask, respectively.

[0021] 3) Add 1.845mmol, 2.505mmol, 3.150mmol, 3.825mmol of N, N'-(4,4'-Methylene-diphenyl)bismaleimide (BMI) and 1.23mmol, 1.67mmol, 2.10mmol, 2.55mmol, 1.67mmol of chain extender FA-FGE Diol to the mixed solution respectively. Finally, the sample PUX (X=1,2,3,4) was obtained. Effect verification (1) Testing of self-healing polyurethane substrate The samples were cut into a size of 25 mm × 25 mm × 1 mm, and then immersed in deionized water at 20°C and 80°C respectively. The water temperature was kept constant and then immersed for 30 days. The weight loss rate was calculated as follows: In the above formula, m1 and m2 are the weights of the original sample and the dried sample after immersion for 30 days, respectively.

[0022] from Figure 3It can be seen that with the increase in the proportion of chain extender FA-FGE Diol, the mass loss in water first decreases and then increases, among which PU2 performs the best.

[0023] All samples were subjected to X-shaped scratching and placed at 130℃ for 24 h. Figure 4 As shown in the figure, the X scratch on PU2 completely disappeared, while other samples still had some relatively clear scratches. According to these test results, PU has better comprehensive performance, so PU2 was selected as the substrate and 1wt% FMWCNTs were subsequently introduced.

[0024] (2) Anti-corrosion performance In a salt spray test chamber, the self-healing polyurethane coating sample containing 1wt% FMWCNTs was subjected to an X-shaped scratch test and a neutral salt spray test was carried out at 80°C for 60 days. Figure 5 The test results show that after 60 days of salt spray testing, the X-shaped scratches on the surface are basically invisible and no corrosion products are observed.

[0025] (3) Anti-cavitation performance like Figure 6 As shown in the figure, at 20°C, PU2 and PU-FM exhibit excellent anti-cavitation corrosion performance. Over time, the cavitation degree of the composite coating tends to stabilize after an initial sharp increase, and the average corrosion rate of the optimal PU-FM stabilizes at 0.056nm / h after reaching a maximum value of 0.1nm / h. At 80°C, the high temperature solution accelerates the cavitation corrosion process, and the maximum corrosion rate appears in 6 hours, while at 20°C it is 12 hours. The average corrosion rate of PU-FM tends to stabilize at 0.14 nm / h after reaching a maximum value of 0.25nm / h.

[0026] (5) Tensile strength test Tensile strength indicates the limit of damage during stretching, and toughness indicates the ability of a material to absorb deformation force during deformation. Using a tensile testing machine, the sample is tested at 20°C and 80°C to obtain tensile strength data, such as Figure 7 As shown, the integral area between the stress-strain curve and the x-axis represents the toughness of the material. The tensile strength of the sample at 20°C is 72MPa and the toughness is 356 MJ / m 3 ; At 80℃, the tensile strength of the sample is 30MPa and the toughness is 100 MJ / m 3 The data show that the tensile strength and toughness are at a high level, thus improving the corrosion resistance and cavitation resistance.

[0027] (4) Self-healing performance Due to the excellent photothermal conversion ability of FMWCNTs, PU-FM can be easily repaired by absorbing near-infrared light (808 nm). 2 After irradiating the fracture surface under near-infrared light (NIR) for 90 seconds, PU-FM was completely repaired. In order to quantitatively evaluate the self-healing ability of PU-FM, the multiple self-healing efficiencies of the coating were evaluated by tensile tests. The self-healing efficiency a was calculated according to the following formula: Where F1 is the tensile strength of the original sample, and F2 is the tensile strength of the damaged sample after self-repair.

[0028] like Figure 8 As shown in the figure, the irradiation time determines the degree of heating of the coating surface, and the self-healing efficiency increases from 70% at 60 s to 93% at 90 s. However, excessive irradiation can cause burning and side reactions, which directly lead to the self-healing efficiency dropping below 50%. The repeatability of the repair was verified by irradiating with near-infrared light for 90 s under the same conditions. Figure 8 It can be seen that although the repair efficiency decreases slightly with repeated cycles, the self-healing efficiency remains at 81% after three repetitions.

Claims

1. A method for preparing an anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments, characterized in that: The specific steps of this method are as follows: 1) Add 1.85-3.17 mmol of polytetrahydrofuran diol with a molecular weight of 1000 g / mol and 4.4 mmol of diphenylmethane diisocyanate into a reaction container, and add ethyl acetate to reduce the viscosity of the reactants, then stir the mixture and heat it at 70° C. for 4 hours under a nitrogen atmosphere to obtain a PU prepolymer; 2) Stirring the PU prepolymer at room temperature for 4 hours, then adding 1.845~3.825mmol of diphenylmethane bismaleimide and 1.23~2.55mmol of chain extender saccharamine-furfuryl glycidyl ether diol to the PU prepolymer, stirring for 1h to obtain a PU solution; adding 1~5wt% of the functionalized carbon nanotubes in the mass of the PU prepolymer into N, N-dimethylformamide, and ultrasonically treating for 1h to obtain a functionalized carbon nanotube / N, N-dimethylformamide blend; then mixing the functionalized carbon nanotube / N, N-dimethylformamide blend with the PU solution, and ultrasonically treating for 1h to obtain a coating; the functionalized carbon nanotubes are dopamine-modified carbon nanotubes; 3) The coating is coated on the substrate, and after curing, the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments is obtained.

2. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: In step 1), the amount of polytetrahydrofuran diol added is 2.73 mmol.

3. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: In step 2), the amount of diphenylmethanebismaleimide added is 2.505 mmol.

4. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: In step 2), the amount of the chain extender glucosamine-furfuryl glycidyl ether diol added is 1.67 mmol.

5. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: In step 2), the preparation steps of the chain extender glucosamine-furfuryl glycidyl ether diol are as follows: First, furfurylamine and furfuryl glycidyl ether are added into a reaction container at a molar ratio of 1:2, and then N, N-dimethylformamide is added to reduce the viscosity of the reactants, and then the reaction is carried out at 80°C for 6 hours to finally obtain the chain extender sugar amine-furfuryl glycidyl ether diol.

6. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: In step 2), the amount of functionalized carbon nanotubes added is 1 wt %.

7. The method for preparing the anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments according to claim 1, characterized in that: The preparation steps of functionalized carbon nanotubes in step 2) are as follows: 400 mg of multi-walled carbon nanotubes were ultrasonically mixed with 80 mL of Tris-butter solution in a beaker for 30 minutes, and then 160 mg of dopamine hydrochloride was added and stirred for 12 hours; after the reaction, the mixture was centrifuged, washed with deionized water and ethanol three times, and dried in a vacuum at 60°C to obtain functionalized carbon nanotubes.

8. An anti-corrosion, anti-cavitation and self-repairing marine protective coating suitable for high temperature environments, prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Self-repairing cross-linked polyurethane and preparation method thereof

    CN111574820A

  • Polyurethane carbon nanotube composite filler for water treatment as well as preparation method and application of polyurethane carbon nanotube composite filler

    CN115636501A

  • Functionalized carbon nanotube / polyurethane composite material and preparation method thereof

    CN116217878A

  • Multifunctional paint with self-repairing, cavitation-erosion-preventing, antifouling and corrosion-preventing properties and coating

    CN116948509A

  • Preparation method of recyclable thermosetting polyurethane composite material

    CN117089034A

Cited By

  • Manufacturing method of water-based high-gloss high-fullness high-hardness gloss oil with mirror surface effect

    CN120137472A

  • Method for making water-based high-gloss, high-fullness, and high-hardness varnish with a mirror effect

    CN120137472B